Synthesis and Activity of Novel Fungicide 2-(3-Chlorophenylcarbamoyl)phenyl Acetate - Zhang, Chixiang; Wang, Zhou; Pu, Bo; Wang, Xuesong; Jiao, Shirong (Asian Journal of Chemistry, 2015)
In the present study, 2-(3-chlorophenylcarbamoyl)phenyl acetate was synthesized by the ammonolysis of 2-(chlorocarbonyl)phenyl acetate. Its structure was confirmed by IR and 1H NMR. Its antifungal activity against Sclerotinia sclerotiorum and Helminthosprium maydis has been determined in the laboratory. The results showed that it had good antifungal activity against the two different pathogenic fungi of plants. Its median effective concentrations (EC50) reached 2 and 3.80 mg L-1, respectively.